2019
DOI: 10.1002/adom.201801696
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Terahertz Metasurface Pure Phase Holograms

Abstract: of applications. Spatial light modulators, which can impose programmable modification of the spatial intensity and/or phase distribution of an optical beam, are commonly used in applications, such as optical information processing, imaging, and communications. However, in the THz frequency range, the development of spatial light modulators remains a great challenge due to the lack of electrooptical materials, although they are urgently requested with the ongoing advancement of THz technology and the identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…In the terahertz and optical spectrum, tiny dimensions and immature technics result in the functional multiplexing facing great difficulties. Although more hardships are confronted compared to merely achieving function tuning, some active metasurfaces with dynamically functional multiplexing have still been implemented [91][92][93][94][95][96].…”
Section: Active Metasurfaces With Dynamically Functional Multiplexingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the terahertz and optical spectrum, tiny dimensions and immature technics result in the functional multiplexing facing great difficulties. Although more hardships are confronted compared to merely achieving function tuning, some active metasurfaces with dynamically functional multiplexing have still been implemented [91][92][93][94][95][96].…”
Section: Active Metasurfaces With Dynamically Functional Multiplexingmentioning
confidence: 99%
“…Measured results of focus shifting and the vertical astigmatism are respectively depicted in Figures 10B,C. For further verifying the mechanical robustness of the lens, the strain field was applied more than 1,000 cycles and no image degradation was observed. More recently, a novel photoexcited approach has been presented and applied to a thin silicon wafer for arbitrary terahertz wavefronts shaping [95], apart from the above electrically controllable metasurfaces. In such a work, inhomogeneity of the metasurface was caused by a local IMT in the silicon wafer, and Femtosecond laser was chosen as the photoexcitation.…”
Section: Active Metasurfaces With Dynamically Functional Multiplexingmentioning
confidence: 99%
“…Since the intrinsic loss of graphene layers, the full reflection phase span of 360°has not been achieved; however, the phase span of 315°is sufficient to provide good performance in holographic applications [67]. Moreover, such a wide phase modulation range has been accomplished without need to any imposed polarization conversion seen in the conventional architectures [68]. The DC voltage needed for tuning the chemical potential of graphene is additionally studied in Supplementary Information B to ensure no breakdown occurs in the structure.…”
Section: Re-programmable Polarizationmultiplexed Meta-hologrammentioning
confidence: 99%
“…Recently, Chen et al proposed a new method for generating wavefronts of arbitrary THz beams, as shown in Figure 8b. The hologram and zoom lens can be realized in real time by dynamically controlling the direction of the resonator [72]. Except as the dielectric metasurface provided, the metal metasurface also has outstanding performance in holographic imaging [73,74].…”
Section: Conventional Bulk Semiconductor Metasurfacementioning
confidence: 99%